Lithium-sulfur battery positive electrode, lithium-sulfur battery and preparation method of lithium-sulfur battery

By using a domain-limited functional layer with a sandwich structure in the positive electrode of the lithium sulfur battery, the migration of lithium polysulfides is restricted by using functional particles wrapped by one-dimensional carbon material, the problems of shuttle effect and volume expansion in lithium sulfur batteries are solved, and higher Coulomb efficiency and more stable cycling performance are achieved.

CN119890215APending Publication Date: 2025-04-25CHINA ENERGY LITHIUM

Patent Information

Application Number
CN202311389570.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In lithium-sulfur batteries, due to the electronic insulation and volume expansion of the process of sulfur generation Li2S, the electrode structure is unstable, the utilization rate of active substances is low, and lithium polysulfide is easily dissolved in the electrolyte, causing a shuttle effect, resulting in capacity attenuation and reduced Coulomb efficiency.

Method used

A lithium-sulfur battery positive electrode is designed, adopting a sandwich structure, with a current collector on one side of the sulfur-containing active material layer and a domain-limiting functional layer on the other side. The domain-limiting functional layer consists of functional particles and a shell formed by a one-dimensional carbon material, allowing lithium ions to pass through and limiting the migration of lithium polysulfides.

Benefits of technology

It effectively solves the shuttle effect problem, slows down the capacity attenuation of lithium-sulfur batteries, improves Coulomb efficiency, and improves the structural stability and cycling performance of the positive electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890215A_ABST
    Figure CN119890215A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium-sulfur battery positive electrode, a lithium-sulfur battery and a preparation method of the lithium-sulfur battery positive electrode. The positive electrode has a sandwich structure, a current collector is arranged on one side of a sulfur-containing active substance layer, a confinement functional layer is arranged on the other side of the sulfur-containing active substance layer, and the confinement functional layer comprises functional particles and a shell formed by winding a one-dimensional carbon material on the functional particles, the functional particles comprise any one or a combination of at least two of metal, metal oxide, metal nitride or metal sulfide. Further, the negative electrode of the lithium-sulfur battery comprises a current collector and a lithium-carbon material layer arranged on the surface of the current collector, and the lithium-carbon material comprises a cocoon body formed by a one-dimensional carbon material and one or more lithium-containing cores contained in the cocoon body. According to the lithium-sulfur battery, the positive electrode and the negative electrode have good adaptability, and the lithium-sulfur battery has excellent cycle performance and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium-sulfur battery positive electrode, a lithium-sulfur battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are currently the most widely used secondary batteries. However, due to the limited specific capacity of the embedded positive and negative electrode materials, their energy density has gradually approached the theoretical limit and is difficult to meet the growing market demand. The theoretical energy density of lithium-sulfur batteries is as high as 2600Wh·kg -1 , which is more than five times the energy density of current commercial lithium-ion batteries. Moreover, sulfur has the advantages of abundant reserves, low cost and non-toxicity, so it has become the focus of research.

[0003] However, the use of sulfur as a positive electrode has the following problems: (1) The electronic insulation of sulfur and its discharge product Li2S2 / Li2S leads to low utilization of active materials; (2) The process of generating Li2S from sulfur is accompanied by an 80% volume expansion, which seriously damages the stability of the electrode structure; (3) The intermediate product lithium polysulfide is easily soluble in the electrolyte and shuttles back and forth between the positive and negative electrodes, which is the so-called "shuttle effect", resulting in loss of active materials at the positive and negative electrodes, battery capacity decay, and reduced Coulombic efficiency. Therefore, researchers have designed and optimized sulfur positive electrode materials to solve the above problems.

[0004] At present, the most widely studied is to develop sulfur carriers and add additives to the positive electrode. Among them, CN104659406A discloses a lithium-sulfur battery, in which a polymer network structure is distributed in the positive electrode of the lithium-sulfur battery, and the polymer network structure tightly fixes the lithium sulfide generated during the discharge process, which can effectively slow down the shuttle effect. CN113839044A discloses a lithium-sulfur battery positive electrode, the positive electrode includes a positive electrode slurry and a current collector, the positive electrode slurry is covered on the surface of the current collector, the positive electrode slurry includes an active material, a conductive agent, a binder, an organic solvent and β-MoTe2, β-MoTe2 improves the redox kinetics of the positive electrode of the lithium-sulfur battery, reduces the internal resistance and charge transfer impedance of the lithium-sulfur battery, and improves the cycle stability of the lithium-sulfur battery. However, the additive is evenly dispersed in the positive electrode, and part of the positive electrode interface is still in direct contact with the electrolyte. The lithium polysulfide generated during the discharge process will still directly enter the electrolyte, causing the shuttle effect, and the volume expansion problem of the process of generating Li2S from sulfur cannot be solved.

[0005] How to develop a positive electrode that can isolate sulfur from the electrolyte, solve the shuttle effect in the process of sulfur generating Li2S, slow down the capacity decay of lithium-sulfur batteries and improve the coulombic efficiency has become an urgent problem to be solved at this stage. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a positive electrode of a lithium-sulfur battery, a lithium-sulfur battery and a preparation method thereof, wherein the positive electrode comprises a sulfur-containing active material layer, a current collector is arranged on one side of the sulfur-containing active material layer, and a confined functional layer is arranged on the other side, having a sandwich structure, wherein the confined functional layer is arranged on the surface of the sulfur-containing active material layer, and comprises functional particles and a shell formed by winding a one-dimensional carbon material around the functional particles, which can firmly confine lithium polysulfide to the positive electrode and solve the problem of the shuttle effect.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a lithium-sulfur battery positive electrode, the positive electrode comprising a sulfur-containing active material layer, a current collector being arranged on one side of the sulfur-containing active material layer, and a confined functional layer being arranged on the other side; the confined functional layer comprises functional particles and a shell formed by winding a one-dimensional carbon material around the functional particles, the functional particles comprising any one of metals, metal oxides, metal nitrides or metal sulfides, or a combination of at least two thereof.

[0009] In the present invention, a confined functional layer is provided on the surface of the sulfur-containing active material layer, and the confined functional layer allows lithium ions to pass through, restricts the passage of lithium polysulfides, and slows down the migration of lithium polysulfides; in terms of composition, the confined functional layer includes a shell formed by a one-dimensional carbon material and functional particles wrapped by the shell, and the one-dimensional carbon material has a certain flexibility, and a porous, high-roughness shell is constructed on the surface of the functional particles, which plays a binding role on the functional particles, and has a good contact with the sulfur-containing active material layer, so that the positive electrode has good structural stability and excellent cycle performance; in addition, the one-dimensional carbon material has a suitable specific surface area, which has a confined effect on lithium polysulfides; the functional particles anchor the lithium polysulfides in the positive electrode by adsorption and catalytically convert the polysulfides in time, so as to avoid the phenomenon that the lithium polysulfides dissolve in the electrolyte and go back and forth between the positive and negative electrodes. The mutual cooperation of the one-dimensional carbon material and the functional particles plays a good confining role on the lithium polysulfides, solves the shuttle effect, slows down the capacity decay of the lithium-sulfur battery, and improves the coulomb efficiency.

[0010] Optionally, the average pore size of the shell constructed by the one-dimensional carbon material is 100nm-2μm, for example, it can be 100nm, 300nm, 400nm, 450nm, 500nm, 550nm, 750nm, 950nm, 1000nm, 1.2μm, 1.5μm, 1.8μm or 2μm, including but not limited to the listed point values, preferably 500nm-1μm.

[0011] Optionally, the one-dimensional carbon material includes a carbon material with a diameter ≤500nm, and the diameter can be 500nm, 450nm, 400nm, 300nm, 350nm, 200nm, 100nm, 50nm, 30nm, 20nm, 10nm, 6nm, 4nm, 2nm or 1nm, etc., including but not limited to the listed point values, preferably 1-300nm, preferably single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes (the diameter of the carbon nanotube refers to its outer diameter) or carbon nanofibers. Any one or a combination of at least two, further preferably single-walled carbon nanotubes and / or double-walled carbon nanotubes, and further preferably the one-dimensional material has excellent flexibility and a better effect in constructing a functional layer.

[0012] Optionally, the D50 of the functional particles is 100nm-100μm, for example, it can be 100nm, 200nm, 300nm, 500nm, 1μm, 5μm, 10μm, 20μm, 30μm, 40μm, 50μm, 70μm, 90μm or 100μm, etc., preferably 300nm-50μm. The size of the functional particles matches the one-dimensional carbon material, which facilitates the winding of the one-dimensional carbon material to form a confined functional material of suitable size. The measurement method of the D50 includes a laser diffraction method.

[0013] Optionally, the metal includes any one of lithium, iron, manganese, ruthenium, cobalt, zinc, vanadium, titanium, chromium, molybdenum or tellurium, or a combination of at least two of them. The metal has good adsorption and catalytic conversion capabilities for lithium polysulfides and a good confinement effect. It is preferably any one of lithium, iron, titanium, vanadium or molybdenum, or a combination of at least two of them.

[0014] Optionally, the confined functional layer is provided in a manner including coating and / or rolling. The specific coating and rolling methods are not limited. Coating may be by blade coating, spraying, or spin coating; rolling may be by cold pressing, hot pressing, or a combination of cold pressing and hot pressing (e.g., cold pressing first and then hot pressing). As long as the functional layer can be provided on the surface of the sulfur-containing active material layer, it falls within the protection scope of the present invention.

[0015] Optionally, the thickness of the confined functional layer is 1-100 μm, for example, it can be 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 40 μm, 45 μm, 50 μm, 80 μm, 90 μm, 100 μm, etc., including but not limited to the listed point values, preferably 5-50 μm.

[0016] Optionally, the thickness of the sulfur-containing active material layer is 5-200 μm, for example, it can be 5 μm, 10 μm, 15 μm, 30 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, etc., including but not limited to the listed point values, preferably 10-100 μm.

[0017] Optionally, the thickness ratio of the confined functional layer to the sulfur-containing active material layer is (0.05-10):1, for example, it can be 0.01:1, 0.05:1, 0.1:1, 0.5:1, 1:1, 2.5:1, 5:1, 7.5:1, 9:1 or 10:1, including but not limited to the listed point values. If the thickness ratio is too small, the problems of shuttle effect and volume expansion cannot be effectively solved; if the thickness ratio is too large, it is not conducive to the transmission of lithium ions and reduces the capacity of the lithium-sulfur battery, preferably (0.1-5):1.

[0018] Optionally, taking the mass of the confined functional layer as 100%, the mass proportion of the functional particles is 1-30%, for example, it can be 1%, 3%, 5%, 7%, 10%, 15%, 18%, 20%, 25% or 30%, including but not limited to the listed point values. If the mass proportion of the functional particles is too small, the anchoring effect of the functional particles on lithium to sulfide is limited; if the mass proportion of the functional particles is too large, there is less one-dimensional carbon material in the functional layer, which reduces the binding force between the confined functional layer and the sulfur-containing active material layer, reduces the cycle performance, and there are more inactive substances in the positive electrode, which is not conducive to the improvement of energy density. Preferably, it is 5-20%.

[0019] Optionally, the current collector includes any one of pure aluminum foil, composite aluminum foil, carbon-coated aluminum foil, perforated aluminum foil, nickel foil, nickel foam, perforated nickel foil, carbon nanotube paper or graphene paper, or a combination of at least two of them. As long as they are commonly used by those skilled in the art, they are applicable to the present application.

[0020] Optionally, the sulfur-containing active material layer includes a positive electrode active material, and the positive electrode active material includes any one of elemental sulfur, a sulfur-based compound, or a sulfur-based complex, or a combination of at least two of them.

[0021] Optionally, the elemental sulfur includes sublimated sulfur and / or high purity sulfur.

[0022] Optionally, the sulfur-based compound includes organic sulfide, Li2S n At least one of (1≤n≤8).

[0023] Optionally, the sulfur-based composite comprises any one or a combination of at least two of a sulfur-carbon composite, a sulfur-conductive polymer composite or a sulfur-inorganic oxide composite, preferably any one or a combination of at least two of sulfurized polyacrylonitrile (SPAN), sulfur-polypyrrole, sulfur-polyacetylene, sulfur-polyurethane or sulfur-polyethylene glycol;

[0024] Optionally, the D50 of the raw material of the positive active material is not equal to the D50 of the raw material of the functional particles in the confined functional layer. In the present invention, the D50 of the raw material of the positive active material can be greater than the D50 of the raw material of the functional particles, or less than the D50 of the raw material of the functional particles. The purpose of this setting is to improve the bonding force between the sulfur-containing active material layer and the confined functional layer.

[0025] In the present application, there is no specific limitation on the type of carbon material in the sulfur-carbon composite, which may be mesoporous carbon, activated carbon, or metal-organic framework (MOF). As long as it is a sulfur-loaded carbon material commonly used by technicians in this field, it is applicable to the present application.

[0026] In a second aspect, the present application provides a lithium-sulfur battery, wherein the lithium-sulfur battery comprises the positive electrode as described in the first aspect above.

[0027] The lithium-sulfur battery of the present application has slow capacity decay, high coulombic efficiency, and excellent cycle performance.

[0028] The present application does not limit the specific configuration of the lithium-sulfur battery, and technicians can adjust it as needed. The electrolyte can be a solid electrolyte or a liquid electrolyte. The solid electrolyte can be a garnet-structured Li x A3B2O 12 , wherein 3≤x≤7, A is potassium, magnesium, calcium, strontium, barium, yttrium, lanthanum, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium or lutetium, and B is zirconium, hafnium, niobium, tantalum, tungsten, indium, tin, antimony, bismuth or tellurium, and may also be a sulfide solid electrolyte such as lithium germanium phosphorus sulfur (LGPS). The liquid electrolyte may be an electrolyte of 1M LiTFSI (DOL / DME=1:1, volume ratio, 1.0wt% LiNO3), or an electrolyte of 1M LiPF6 (EC / DMC / DEC=1:1:1, volume ratio, 1.0wt% VC).

[0029] The lithium-sulfur battery separator can be polypropylene, polyethylene, or modified polypropylene or modified polyethylene, such as polypropylene with a montmorillonite coating. As long as it is a type commonly used by technicians in this field, it is suitable for this application.

[0030] Optionally, the lithium-sulfur battery further comprises a negative electrode, and the negative electrode comprises any one or a combination of at least two of a metal lithium strip, a lithium alloy strip or a lithium carbon composite strip, preferably a lithium alloy strip and / or a lithium carbon composite strip. For example, the negative electrode can be any one or a combination of at least two of a lithium foil, a lithium sheet, a lithium strip, a lithium copper composite strip, a lithium alloy foil, a lithium alloy sheet, a lithium alloy strip, a lithium alloy copper composite strip, a lithium carbon foil, a lithium carbon sheet, a lithium carbon strip, and a lithium carbon copper composite strip, preferably any one or a combination of at least two of a lithium copper composite strip, a lithium alloy copper composite strip or a lithium carbon composite strip.

[0031] The lithium-copper composite belt has a good current collecting effect. The lithium-alloy-copper composite belt not only has a good current collecting effect, but the alloy elements can also regulate the uniform deposition of metallic lithium and inhibit the growth of lithium dendrites. The lithium-carbon composite belt has good conductivity and stability, and the carbon skeleton regulates the current density to be uniform, inhibiting the growth of lithium dendrites while also alleviating volume expansion.

[0032] As a preferred technical solution of the present application, the lithium-carbon composite belt includes a composite belt in which carbon material is uniformly dispersed in a lithium-containing material and / or a composite belt formed by rolling the carbon material wrapped around the surface of lithium-containing particles (i.e., lithium-carbon material with a cocoon structure), preferably a composite belt formed by rolling the carbon material wrapped around the surface of lithium-containing particles (i.e., lithium-carbon material with a cocoon structure).

[0033] Optionally, the carbon material in the lithium-carbon composite belt includes any one or a combination of at least two of granular, flaky, tubular or linear nanocarbon materials, preferably any one or a combination of at least two of Ketjen black, acetylene black, conductive graphite, graphene, modified graphene, carbon nanotubes, modified carbon nanotubes, carbon nanofibers or modified carbon nanofibers.

[0034] Optionally, the lithium-containing particles include metallic lithium powder and / or lithium alloy powder, and the lithium alloy powder includes lithium and any one or a combination of at least two of magnesium, aluminum, tin, silver, indium, silicon or boron.

[0035] Optionally, the D50 of the lithium-containing particles is 1-100 μm, for example, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 40 μm, 45 μm, 50 μm, 80 μm, 90 μm, 100 μm, etc., including but not limited to the listed point values, preferably 5-50 μm.

[0036] In a third aspect, the present application provides a method for preparing a lithium-sulfur battery as described in the second aspect above, the method comprising the following steps:

[0037] (1) A sulfur-containing active material, a conductive agent, a binder and a solvent are mixed to prepare a positive electrode slurry, and then the positive electrode slurry is coated on the surface of a current collector to obtain a current collector-sulfur-containing active material layer:

[0038] (2) High-speed dispersion and / or spray granulation of functional particles, one-dimensional carbon materials and solvents to obtain functional particles (referred to as limiting particles) wrapped by the one-dimensional carbon materials (forming a shell), which are then coated and / or rolled on the surface of the current collector-sulfur-containing active material layer to obtain a positive electrode;

[0039] (3) The positive electrode, negative electrode and separator in step (1) are made into a bare battery cell, and then the bare battery cell is put into a shell / bag, baked, injected with liquid, allowed to stand, formed, and shaped to obtain the lithium-sulfur battery.

[0040] In the present invention, the types of the sulfur-containing active material, the conductive agent, the binder and the solvent in step (1) are not specifically limited. The sulfur-containing active material can be elemental sulfur, a sulfur-carbon composite, or vulcanized polyacrylonitrile; the conductive agent can be Ketjen black, acetylene black, or Super P; the binder can be polyvinylidene fluoride (PVDF), LA133, or styrene-butadiene rubber (SBR); the solvent can be water or N-methylpyrrolidone, and any type commonly used by those skilled in the art is applicable to the present application.

[0041] Optionally, the solvent in step (2) includes any one of water, ethanol, N-methylpyrrolidone, liquid alkanes with a carbon number of 1-10, p-xylene, N,N-dimethylformamide or tetrahydrofuran, or a combination of at least two thereof.

[0042] Optionally, the rotation speed of the high-speed dispersion in step (2) is 6000-15000 rpm, for example, it can be 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm, 10000 rpm, 11000 rpm, 12000 rpm, 14000 rpm or 15000 rpm, etc., preferably 8000-12000 rpm.

[0043] Optionally, the high-speed dispersion time in step (2) is 1-30 min, for example, 1 min, 3 min, 5 min, 10 min, 15 min, 20 min, 25 min or 30 min, etc., preferably 5-20 min.

[0044] For example, the coating in step (2) includes the following steps:

[0045] The limiting particles, a binder such as PVDF and a solvent such as N-methylpyrrolidone are uniformly mixed, and a conductive agent such as Ketjen black is optionally added to obtain a slurry, and the slurry is coated on the surface of the sulfur-containing active material layer to obtain a positive electrode.

[0046] For example, the rolling in step (2) includes the following steps:

[0047] The limiting particles, PTFE and other binders, and optionally, a conductive agent such as Ketjen black are added to fiberize the binder, and then hot-pressed into a confined functional layer, and the confined functional layer is rolled onto the surface of the sulfur-containing active material layer to obtain a positive electrode.

[0048] Compared with the prior art, the present invention has at least the following beneficial effects:

[0049] (1) The positive electrode of the lithium-sulfur battery provided by the present invention has a sandwich structure, and a confined functional layer is arranged on the surface of the sulfur-containing active material layer, wherein the confined functional layer allows lithium ions to pass through, restricts the passage of lithium polysulfides, slows down the migration of lithium polysulfides, and alleviates the shuttle effect;

[0050] (2) In the positive electrode of the lithium-sulfur battery provided by the present invention, the one-dimensional carbon material in the confined functional layer constrains, limits or improves the conductivity of the functional particles, and at the same time improves the roughness of the surface, thereby improving the binding force with the sulfur-containing active material layer. The positive electrode has good structural stability, which is conducive to improving the cycle performance;

[0051] (3) In the positive electrode of the lithium-sulfur battery provided by the present invention, the one-dimensional carbon material has a suitable specific surface area, which has a confinement effect on lithium polysulfides. The functional particles anchor the lithium polysulfides in the positive electrode and are insoluble in the electrolyte. The two cooperate with each other to play a good confinement role on lithium polysulfides, solve the shuttle effect, slow down the capacity decay of the lithium-sulfur battery and improve the Coulomb efficiency;

[0052] (4) The present invention further improves the coulombic efficiency of the positive electrode of the lithium-sulfur battery and slows down the capacity decay by selecting one-dimensional carbon materials and functional particles, and regulating parameters such as the thickness of the confined functional layer and the mass ratio of the functional particles;

[0053] (5) The preparation method provided by the present invention is simple to operate, has high production efficiency, and has industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 A schematic structural diagram of a positive electrode of a lithium-sulfur battery provided by the present invention;

[0055] Figure 2 This is the SEM image of the confined functional material in Example 1;

[0056] 1-current collector, 2-sulfur-containing active material layer, 3-confined functional layer, 31-functional particles, 32-shell. DETAILED DESCRIPTION

[0057] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0058] For example, the present invention provides a lithium-sulfur battery positive electrode, the structural schematic diagram of which is as follows Figure 1 The positive electrode comprises a sulfur-containing active material layer 2, a current collector 1 is arranged on one side of the sulfur-containing active material layer 2, and a confined functional layer 3 is arranged on the other side; the confined functional layer 3 is formed of a confined functional material, and the confined functional material comprises functional particles 31 and a shell 32 formed of a one-dimensional carbon material wrapped around the functional particles 31.

[0059] Example 1

[0060] The present embodiment provides a lithium-sulfur battery, wherein the positive electrode active material of the lithium-sulfur battery is sulfurized polyacrylonitrile (SPAN) with a thickness of 100 μm, the confined functional layer includes metal lithium powder with a D50 of 50 μm wrapped by single-walled carbon nanotubes and a thickness of 5 μm, and the mass of the metal lithium powder accounts for 5% of the mass of the confined functional layer; the negative electrode active material is a 50 μm pure lithium strip, the electrolyte is 1 mol / L LiPF6, the solvent is a mixture of EC, DMC and DEC in a volume ratio of 1:1:1, the additive is 1 wt% ascorbic acid (VC), and the separator is polypropylene.

[0061] The preparation method of the lithium-sulfur battery comprises the following steps:

[0062] (1) Sulfurized polyacrylonitrile (sulfur content of 49 wt%, homemade) with a D50 of 200 nm, acetylene black, and PVDF were mixed in a mass ratio of 7:2:1, with N-methylpyrrolidone as the solvent to prepare a slurry, which was then coated on the surface of a 10 μm aluminum foil and dried at 70° C. to obtain an aluminum foil-sulfurized polyacrylonitrile layer;

[0063] (2) In a glove box filled with argon, metallic lithium powder, single-walled carbon nanotubes and p-xylene were mixed and stirred at a speed of 6000 rpm for 2 min to obtain a metallic lithium powder mixture wrapped with single-walled carbon nanotubes (referred to as a confined functional material, whose SEM characterization is as follows: Figure 2 As shown), the mixture is rolled on the surface of the aluminum foil-sulfurized polyacrylonitrile layer, and vacuum-dried at 70° C. to obtain a positive electrode;

[0064] (3) In a glove box filled with argon, a punching machine was used to punch the positive electrode into a positive electrode sheet with a diameter of 14 mm, and a 50 μm pure lithium strip was punched into a negative electrode sheet with a diameter of 16 mm. The sheets were assembled with a polypropylene separator with a diameter of 19 mm and an electrolyte into a button-type lithium-sulfur battery.

[0065] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li + ), the initial discharge capacity at 0.2C is 810mAh / g, the discharge capacity after 100 cycles is 656mAh / g, and the capacity retention rate is 80.99%.

[0066] Example 2

[0067] The present embodiment provides a lithium-sulfur battery, wherein the positive electrode active material of the lithium-sulfur battery is a sulfur-carbon nanotube ball composite material with a thickness of 50 μm, and the confined functional layer includes vanadium pentoxide with a D50 of 1 μm wound by double-walled carbon nanotubes, with a thickness of 50 μm, and the mass of the vanadium pentoxide accounts for 30% of the mass of the confined functional layer; the negative electrode active material is a 50 μm pure lithium carbon ribbon (self-made), the electrolyte is 1 mol / L LiTFSI, the solvent is a mixture of DOL and DME in a volume ratio of 1:1, and 1 wt% LiNO3 is added.

[0068] The preparation method of the lithium-sulfur battery comprises the following steps:

[0069] (1) A sulfur-carbon nanotube ball composite material with a D50 of 5 μm (sulfur content of 49 wt%, homemade), acetylene black, and PVDF were mixed in a mass ratio of 7:2:1, with N-methylpyrrolidone as the solvent to prepare a slurry, which was then coated on the surface of a 10 μm carbon-coated aluminum foil and dried at 70° C. to obtain a carbon-coated aluminum foil-sulfur-carbon nanotube ball layer;

[0070] (2) mixing vanadium pentoxide, double-walled carbon nanotubes and N-methylpyrrolidone, stirring at a rotation speed of 8000 rpm for 30 minutes to obtain a mixture of vanadium pentoxide wrapped with double-walled carbon nanotubes, mixing the mixture with PVDF glue, coating the mixture on the surface of the carbon-coated aluminum foil-sulfur-carbon nanotube ball layer, and drying at 70° C. to obtain a positive electrode;

[0071] (3) In a glove box filled with argon, a punching machine is used to punch the positive electrode into a positive electrode sheet with a diameter of 14 mm, and a 50 μm lithium carbon ribbon (the raw material of the lithium carbon ribbon is a cocoon-structured lithium carbon particle, which is formed by roller pressing, and the cocoon-structured lithium carbon particle includes a cocoon body formed by single-walled carbon nanotubes and at least one metal lithium particle contained in the cocoon body) is punched into a negative electrode sheet with a diameter of 16 mm, and assembled with a polypropylene separator with a diameter of 19 mm and an electrolyte into a button-type lithium-sulfur battery.

[0072] The voltage range is 1.0-3.0V (vs.Li / Li + ), the initial discharge capacity at 0.2C is 809 mAh / g, the discharge capacity after 100 cycles is 663 mAh / g, and the capacity retention rate is 81.95%.

[0073] Example 3

[0074] The present embodiment provides a lithium-sulfur battery, wherein the positive electrode active material of the lithium-sulfur battery is sublimated sulfur with a thickness of 10 μm, and the confined functional layer includes molybdenum disulfide with a D50 of 300 nm co-wound by single-walled carbon nanotubes and carbon nanofibers, with a thickness of 100 μm, and the mass of the molybdenum disulfide accounts for 20% of the mass of the confined functional layer; the negative electrode active material is a 50 μm lithium-tin alloy strip (self-made), and the electrolyte is a lithium germanium phosphorus sulfur (LGPS) sulfide solid electrolyte.

[0075] The preparation method of the lithium-sulfur battery comprises the following steps:

[0076] (1) Sublimed sulfur with a D50 of 20 μm, acetylene black, and PVDF are mixed in a mass ratio of 7:2:1, with N-methylpyrrolidone as the solvent to prepare a slurry, which is then coated on the surface of a 10 μm carbon-coated aluminum foil and dried at 70° C. to obtain a carbon-coated aluminum foil-sublimated sulfur layer;

[0077] (2) Molybdenum disulfide, single-walled carbon nanotubes, carbon nanofibers and tetrahydrofuran are mixed, stirred at a rotation speed of 12000 rpm for 20 min to obtain a molybdenum disulfide mixture of single-walled carbon nanotubes and carbon nanofibers, the mixture is mixed with SEBS (SEBS is a linear triblock copolymer with polystyrene as the terminal segment and ethylene-butylene copolymer obtained by hydrogenation of polybutadiene as the middle elastic block) glue, coated on the surface of the carbon-coated aluminum foil-sulfur-mesoporous carbon layer, and dried at 70° C. to obtain a positive electrode;

[0078] (3) In a glove box filled with argon, a punching machine was used to punch the positive electrode into a positive electrode sheet with a diameter of 14 mm, and a 50 μm lithium-tin (8.9 wt% tin) alloy strip was punched into a negative electrode sheet with a diameter of 16 mm. The sheets were assembled with a polypropylene diaphragm LGPS electrolyte membrane with a diameter of 19 mm to form a button-type lithium-sulfur battery.

[0079] At 60°C, the voltage range is 1.0-3.0V (vs. Li / Li + ), the initial discharge capacity at 0.2C is 1211 mAh / g, the discharge capacity after 100 cycles is 987 mAh / g, and the capacity retention rate is 81.50%.

[0080] Example 4

[0081] Compared with Example 2, the only difference is that the thickness of the confined functional layer is replaced with 3 μm, and the other conditions are the same as those of Example 2.

[0082] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li +), the initial discharge capacity at 0.2C is 810mAh / g, the discharge capacity after 100 cycles is 590mAh / g, and the capacity retention rate is 72.84%. Compared with Example 1, the cycle performance of this embodiment is poor, because the thickness of the confined functional layer is too small, the confinement effect on lithium polysulfide is limited, and the effect on solving the shuttle effect and volume expansion problem is limited.

[0083] Example 5

[0084] Compared with Example 2, the only difference is that the thickness of the confined functional layer is replaced with 300 μm, and the other conditions are the same as those of Example 2.

[0085] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li + ), the initial discharge capacity at 0.2C is 803mAh / g, the discharge capacity after 100 cycles is 634mAh / g, and the capacity retention rate is 78.95%. Compared with Example 2, the initial discharge capacity and cycle performance of this embodiment are poor, because the thickness of the confined functional layer is too large, which is not conducive to the transmission of lithium ions and the performance of the capacity of the positive electrode active material.

[0086] Example 6

[0087] Compared with Example 2, the only difference is that the mass proportion of vanadium pentoxide in the confined functional layer is replaced by 2%, and the other conditions are the same as those in Example 2.

[0088] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li + ), the initial discharge capacity at 0.2C is 809 mAh / g, the discharge capacity after 100 cycles is 603 mAh / g, and the capacity retention rate is 74.54%. Compared with Example 2, the cycle performance of this embodiment is poor, because the mass proportion of the functional particle vanadium pentoxide is too small, the anchoring effect on lithium polysulfide is limited, and the shuttle effect cannot be effectively solved.

[0089] Example 7

[0090] Compared with Example 2, the only difference is that the mass proportion of vanadium pentoxide in the confined functional layer is replaced with 20%, and the other conditions are the same as those in Example 2.

[0091] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li +), the initial discharge capacity at 0.2C is 809 mAh / g, the discharge capacity after 100 cycles is 676 mAh / g, and the capacity retention rate is 83.56%. Compared with Example 2, the cycle performance of this embodiment is better, because the mass proportion of the functional particle metal lithium powder is more appropriate, the anchoring effect on lithium polysulfide is good, and the shuttle effect is effectively solved.

[0092] Example 8

[0093] Compared with Example 2, the only difference is that the lithium carbon ribbon is replaced by a pure lithium ribbon, and the other conditions are the same as those in Example 2.

[0094] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li + ), the initial discharge capacity at 0.2C is 809 mAh / g, the discharge capacity after 100 cycles is 596 mAh / g, and the capacity retention rate is 73.67%. Compared with Example 2, the cycle performance of this embodiment is poor, because the pure lithium belt has no cocoon, cannot alleviate the expansion of metallic lithium, and cannot regulate the current density and inhibit the growth of lithium dendrites.

[0095] Example 9

[0096] Compared with Example 2, the only difference is that the lithium carbon ribbon is replaced by a lithium magnesium alloy ribbon (20 wt % magnesium), and the other conditions are the same as those in Example 2.

[0097] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li + ), the initial discharge capacity at 0.2C is 809 mAh / g, the discharge capacity after 100 cycles is 672 mAh / g, and the capacity retention rate is 83.07%. Compared with Example 2, the cycle performance of this embodiment is better, because the magnesium in the pure lithium-magnesium alloy strip can regulate the uniform deposition of metallic lithium, and the atomic radius of lithium and magnesium is quite different, which is conducive to the transmission of lithium.

[0098] Example 10

[0099] Compared with Example 2, the only difference is that the lithium carbon ribbon is replaced by a lithium-magnesium alloy carbon ribbon (20wt% magnesium), the raw material of the lithium-magnesium alloy carbon ribbon is a cocoon-structured lithium-carbon material, the raw material is formed by roller pressing, and the cocoon-structured lithium-carbon particles include a cocoon body formed by single-walled carbon nanotubes and lithium-magnesium alloy particles contained in the cocoon body. The other conditions are the same as those in Example 2.

[0100] The preparation method of the cocoon-structured lithium carbon comprises: (1) dispersing single-walled carbon nanotubes and p-xylene at a high speed of 8000 rpm for 30 minutes; (2) adding lithium-magnesium alloy powder with a D50 of 30 μm and mixing at 6000 rpm for 15 minutes to obtain a lithium-magnesium alloy wrapped with single-walled carbon nanotubes, i.e., a lithium-carbon material with a cocoon structure.

[0101] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li + ), the initial discharge capacity at 0.2C is 809 mAh / g, the discharge capacity after 100 cycles is 682 mAh / g, and the capacity retention rate is 84.30%. Compared with Example 2, the cycle performance of this embodiment is better, because the magnesium in the pure lithium-magnesium alloy strip can regulate the uniform deposition of metallic lithium, and the atomic radius of lithium and magnesium is quite different, which is conducive to the transmission of lithium.

[0102] Comparative Example 1

[0103] Compared with Example 2, the only difference is that the positive electrode is not provided with a confined functional layer, and the other conditions are the same as those of Example 2.

[0104] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li + ), the initial discharge capacity at 0.2C is 809 mAh / g, the discharge capacity after 100 cycles is 543 mAh / g, and the capacity retention rate is 67.12%. Compared with Example 2, the cycle performance of this comparative example is poor, because there is no confined functional layer on the surface of the positive electrode, there is no confinement effect on lithium polysulfide, and the shuttle effect is significant.

[0105] Comparative Example 2

[0106] Compared with Example 2, the only difference is that the vanadium pentoxide wrapped with double-walled carbon nanotubes is uniformly dispersed between the sulfur-carbon nanotube balls of the positive electrode active material, and the other conditions are the same as those in Example 2.

[0107] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li + ), the initial discharge capacity at 0.2C is 809 mAh / g, the discharge capacity after 100 cycles is 610 mAh / g, and the capacity retention rate is 75.40%. Compared with Example 2, the cycle performance of this comparative example is poor, because the vanadium pentoxide coated with double-walled carbon nanotubes is uniformly dispersed between the sulfur-carbon nanotube balls of the positive electrode active material, and the anchoring effect on lithium polysulfide is poorer than that of Example 2.

[0108] Comparative Example 3

[0109] Compared with Example 2, the only difference is that the vanadium pentoxide wrapped with double-walled carbon nanotubes is replaced by double-walled carbon nanotubes, and the other conditions are the same as those in Example 2.

[0110] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li + ), the initial discharge capacity at 0.2C is 809 mAh / g, the discharge capacity after 100 cycles is 565 mAh / g, and the capacity retention rate is 69.84%. Compared with Example 2, the cycle performance of this comparative example is poor, because only the double-walled carbon nanotubes play a role, and the restriction effect on lithium polysulfide is limited.

[0111] Comparative Example 4

[0112] Compared with Example 2, the only difference is that the vanadium pentoxide wrapped with double-walled carbon nanotubes is replaced by vanadium pentoxide, and the other conditions are the same as those in Example 2.

[0113] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li + ), the initial discharge capacity at 0.2C is 809 mAh / g, the discharge capacity after 100 cycles is 581 mAh / g, and the capacity retention rate is 71.82%. Compared with Example 2, the cycle performance of this comparative example is poor, because vanadium pentoxide only anchors lithium polysulfide, but its conductivity and binding force with sulfur-carbon nanotubes are worse than those of Example 2.

[0114] Comparative Example 5

[0115] Compared with Example 2, the only difference is that the double-walled carbon nanotubes and vanadium pentoxide are uniformly dispersed between the positive electrode active material sulfur-carbon nanotube balls, and the other conditions are the same as those in Example 2.

[0116] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li + ), the initial discharge capacity at 0.2C is 809 mAh / g, the discharge capacity after 100 cycles is 592 mAh / g, and the capacity retention rate is 73.18%. Compared with Example 2, the cycle performance of this comparative example is poor, because the double-walled carbon nanotubes and vanadium pentoxide are evenly dispersed between the positive electrode active material sulfur-carbon nanotube balls, and the two play their own role, and the effect of the two cooperating with each other in Example 2 cannot be achieved.

[0117] Comparative Example 6

[0118] Compared with Example 2, the only difference is that the double-walled carbon nanotubes are replaced by graphene nanosheets (Beijing Meiston Technology Development Co., Ltd., model SY-GNP-S), and the other conditions remain unchanged.

[0119] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li + ), the initial discharge capacity at 0.2C is 809mAh / g, the discharge capacity after 100 cycles is 574mAh / g, and the capacity retention rate is 70.95%. Compared with Example 2, the cycle performance of this comparative example is poor, because the graphene nanosheet is a two-dimensional carbon material with a large specific surface area, which is conducive to the transmission of lithium polysulfide, and the effect is worse than that of one-dimensional carbon material; at the same time, the shell constructed by the graphene nanosheet has a low roughness, and the bonding effect with the sulfur-containing active material layer is worse than that of the shell constructed by the one-dimensional carbon material.

[0120] Comparative Example 7

[0121] Compared with Example 2, the only difference is that vanadium pentoxide is replaced by silicon dioxide (Aladdin S433673), and the other conditions remain unchanged.

[0122] At 25°C, the voltage range is 1.0-3.0V (vs. Li / Li + ), the initial discharge capacity at 0.2C is 809 mAh / g, the discharge capacity after 100 cycles is 558 mAh / g, and the capacity retention rate is 68.97%. Compared with Example 2, the cycle performance of this comparative example is poor, because silicon dioxide is a non-metallic functional particle, which only plays an adsorption role and has no catalytic conversion ability, and its effect is worse than that of vanadium pentoxide.

[0123] The applicant declares that the present invention illustrates the detailed structural features of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structural features, that is, it does not mean that the present invention must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A lithium-sulfur battery positive electrode, characterized in that: The positive electrode comprises a sulfur-containing active material layer, a current collector is arranged on one side of the sulfur-containing active material layer, and a confinement functional layer is arranged on the other side; The confined functional layer is formed by a confined functional material, which includes functional particles and a shell formed by a one-dimensional carbon material wrapped around the functional particles. The functional particles include any one of metals, metal oxides, metal nitrides or metal sulfides, or a combination of at least two of them.

2. The positive electrode according to claim 1, characterized in that The one-dimensional carbon material comprises a carbon material with a diameter of ≤500 nm, preferably any one of single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes or carbon nanofibers or a combination of at least two thereof, and more preferably single-walled carbon nanotubes and / or double-walled carbon nanotubes; Preferably, the D50 of the functional particles is 100nm-100μm, preferably 300nm-50μm; Preferably, the metal includes any one of lithium, iron, manganese, ruthenium, cobalt, zinc, vanadium, titanium, chromium, molybdenum or tellurium or a combination of at least two thereof, preferably any one of lithium, iron, titanium, vanadium or molybdenum or a combination of at least two thereof.

3. The positive electrode according to claim 1 or 2, characterized in that The method of setting the confined functional layer includes coating and / or rolling; Preferably, the thickness of the confined functional layer is 1-100 μm, preferably 5-50 μm; Preferably, the thickness of the sulfur-containing active material layer is 5-200 μm, preferably 10-100 μm; Preferably, the thickness ratio of the confined functional layer to the sulfur-containing active material layer is (0.05-10):1, preferably (0.1-5):1; Preferably, based on the mass of the confined functional layer being 100%, the mass of the functional particles accounts for 1-30%, preferably 5-20%.

4. The positive electrode according to any one of claims 1 to 3, characterized in that The current collector includes any one of pure aluminum foil, composite aluminum foil, carbon-coated aluminum foil, perforated aluminum foil, nickel foil, foamed nickel, perforated nickel foil, carbon nanotube paper or graphene paper, or a combination of at least two of them.

5. The positive electrode according to any one of claims 1 to 4, characterized in that The sulfur-containing active material layer includes a positive electrode active material, and the positive electrode active material includes any one of elemental sulfur, a sulfur-based compound, or a sulfur-based complex, or a combination of at least two thereof; Preferably, the elemental sulfur includes sublimated sulfur and / or high-purity sulfur; Preferably, the sulfur-based compound includes organic sulfide, Li2S n At least one of (1≤n≤8); Preferably, the sulfur-based composite comprises any one or a combination of at least two of a sulfur-carbon composite, a sulfur-conductive polymer composite or a sulfur-inorganic oxide composite, preferably sulfurized polyacrylonitrile; Preferably, the D50 of the raw material of the positive electrode active material is not equal to the D50 of the raw material of the functional particles in the confined functional layer.

6. A lithium-sulfur battery, characterized in that: The lithium-sulfur battery comprises the positive electrode as described in any one of claims 1 to 5 above.

7. The lithium-sulfur battery according to claim 6, characterized in that: The lithium-sulfur battery further comprises a negative electrode, which comprises any one of a metal lithium strip, a lithium alloy strip or a lithium-carbon composite strip, or a combination of at least two of them, preferably a lithium alloy and / or a lithium-carbon composite material.

8. The lithium-sulfur battery according to claim 7, characterized in that: The lithium-carbon composite belt comprises a composite belt in which carbon material is uniformly dispersed in a lithium-containing material and / or a composite belt formed by rolling a carbon material wrapped around the surface of lithium-containing particles, preferably a composite belt formed by rolling a carbon material wrapped around the surface of lithium-containing particles; Preferably, the carbon material in the lithium-carbon composite belt includes any one or a combination of at least two of granular, flaky, tubular or linear nanocarbon materials; Preferably, the lithium-containing particles include metallic lithium powder and / or lithium alloy powder, and the lithium alloy powder includes lithium and any one or a combination of at least two of magnesium, aluminum, tin, silver, indium, silicon or boron; Preferably, the D50 of the lithium-containing particles is 1-100 μm, preferably 5-50 μm.

9. A method for preparing a lithium-sulfur battery as claimed in any one of claims 6 to 8, characterized in that: The method comprises the following steps: (1) A sulfur-containing active material, a conductive agent, a binder and a solvent are mixed to prepare a positive electrode slurry, and then the positive electrode slurry is coated on the surface of a current collector to obtain a current collector-sulfur-containing active material layer: (2) high-speed dispersion and / or spray granulation of functional particles, one-dimensional carbon materials and solvents to obtain a confined functional material including functional particles and a shell formed by winding the one-dimensional carbon material around the functional particles, and coating and / or rolling the confined functional material on the surface of the current collector-sulfur-containing active material layer to obtain a positive electrode; (3) The positive electrode, negative electrode and separator in step (1) are made into a bare battery cell, and then the bare battery cell is put into a shell / bag, baked, injected with liquid, allowed to stand, formed, and shaped to obtain the lithium-sulfur battery.

10. The method according to claim 9, characterized in that The solvent in step (2) includes any one of water, ethanol, N-methylpyrrolidone, liquid alkanes with 1 to 10 carbon atoms, p-xylene, N,N-dimethylformamide or tetrahydrofuran, or a combination of at least two thereof; Preferably, the speed of the high-speed dispersion in step (2) is 6000-15000 rpm, preferably 8000-12000 rpm; Preferably, the high-speed dispersion time in step (2) is 1-30 min, preferably 5-20 min.

Citation Information

Patent Citations

  • Lithium-sulfur battery and preparation method thereof

    CN104659406A

  • Lithium-sulfur battery positive electrode, preparation method thereof and lithium-sulfur battery

    CN113839044A

Cited By

  • Pre-lithiated negative electrode, preparation method thereof and battery

    CN120453301A

  • A pre-lithiation negative electrode and its preparation method and battery

    CN120453301B